Palm oil-based compound as environmentally friendly plasticizer for poly(vinyl chloride) - Ang, D.T.C.; Khong, Y.K.; Gan, S.N. (John Wiley & Sons, 2016)
Many plasticizers have been invented to serve the purpose of making poly(vinyl chloride) (PVC) into a more flexible plastic. In this work, the potential of palm oil-based compound (Palm1) as a polymeric plasticizer for PVC was investigated. Plasticization of PVC was conducted via the solvent casting technique, using tetrahydrofuran (THF) as the mutual solvent. Fourier transform infrared (FTIR) spectroscopy and differential scanning calorimetry (DSC) were used to find evidence of interactions between the plasticizer and PVC. Transition temperatures (Tgs) of the plasticized PVC were obtained using DSC, and their thermal stabilities were evaluated using a thermogravimetric analyzer (TGA). Results from the study show that the polymeric plasticizer could interact with PVC chains via polar interaction involving -C-Cl of PVC and possibly the -OH groups of Palm1. Tg of the PVC was reduced after it was plasticized with Palm1. The results obtained from this study suggest that the Palm1 may have the potential to serve as an environmentally friendly plasticizer for PVC.